The Effectiveness of Interactive Teaching Materials on Jurisprudence Subjects at YASMU Tsanawiyah Madrasah - Tarsono, Tarsono; Algifari, Muhaemin; Fauzan, Muhammad Naufal; Zaki, Muhammad Haikal (CV. Rayyan Dwi Bharata, 2025)
Law Number 20 of 2003 emphasizes the importance of improving the quality of learning to develop students' potential. Effective learning involves cognitive, affective and psychomotor aspects and is supported by components such as objectives, materials, strategies and learning evaluation. Teaching materials play an important role in this process. This research evaluates the effectiveness of visual teaching materials on the cognitive outcomes of Fiqh lessons at MTs YASMU using a quasi-experimental method. Two classes, the control class (conventional method) and the experimental class (visual teaching materials), were compared through a post-test. Statistical analysis using the Mann-Whitney U Test revealed significant differences in cognitive outcomes between the two groups. Students who study with visual teaching materials show better results compared to students who study with conventional methods. These findings indicate that the use of visual teaching materials can improve the quality of learning and student learning outcomes. The application of interactive teaching materials in the curriculum is recommended to improve the quality of education.